A New Intrinsic Complexity Metric for Air Traffic De-Conflicting - Zombre, Patrice; Delahaye, Daniel; Tapamo, Jules-Raymond; Olanweraju, Oludolapo A.; Mora-Camino, Felix (IEEE/AIAA Digital Avionics Systems Conference, 2024)
This study in in the field of Air Traffic Flow Management and considers mainly the pre-tactical planning level of air traffic flows where their global balance is already fixed (flows structures and levels, control sectors and capacity) and where flights are treated on an individual basis in the space between the different departure/arrival airports. Then, for each flight, decisions such as departure rescheduling and/or rerouting may be taken by the Air Traffic Flow Management to cope with predicted traffic congestion situations resulting in conflicts. The adopted objective is the global reduction of interactions between flights while maintaining as much as possible the original efficiency of flight plans computed by airlines. A measure of the criticality of the separation between two aircrafts is introduced as a basis to construct new air traffic complexity measures, either local or global, either instantaneous or integrated over periods of time. It is shown in this study how the resulting metric can be used to perform through standard maneuvers the de-confliction of enroute air traffic over a given area and during a given time window. Two approaches are considered, one which is global and leads to the resolution of a large nonlinear optimization problem, and another one which is decentralized and makes use of directional components of the aircraft centric and flight centric complexity indexes. Then, in the case of flight centric traffic control, using the new flight centric complexity measure, the assignment of flights to the different controllers in charge of the monitoring of an extended area is formulated as an optimal partitioning problem where interactions between controllers must be minimized. To cope quickly with this combinatorial problem, a heuristic approach is developed.